The secret of Sabrina Fludde - Fisk, Pauline (New York : Bloomsbury : Distributed to the trade by St. Martin's Press, 2002)
A girl who has lost her memory makes new friends in an English town and finds her own way of discovering who she is.
Published in Great Britain under title: Sabrina Fludde.
Booklist
Publisher's Weekly
Wilson's Junior High School
6.2
5-8
Keywords: Amnesia -- Fiction; Identity -- Fiction; Amnesia -- Fiction; Identity (Psychology) -- Fiction; England -- Fiction; England -- Fiction